2021
DOI: 10.1155/2021/6688855
|View full text |Cite|
|
Sign up to set email alerts
|

Antioxidant Effect of Polygonatum sibiricum Polysaccharides in D-Galactose-Induced Heart Aging Mice

Abstract: Polygonatum sibiricum polysaccharides (PSP), the extract of Polygonatum sibiricum, are demonstrated to exhibit a wide range of pharmacological activities. A recent study reported that PSP alleviated the aging of the kidney and meninges. However, the effect of PSP on heart aging remains unclear. The present study is aimed at investigating the protection of PSP on D-galactose- (D-gal-) induced heart aging. Results showed that irregularly arranged cardiac muscle fibers were observed in heart tissues of D-gal-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 34 publications
0
38
0
1
Order By: Relevance
“…T-AOC is an important nonenzymatic antioxidant, and its decreased levels are associated with a reduced resistance of the body’s antioxidant defense system against free radicals [ 38 ]. T-SOD is a free radical scavenging enzyme in vivo key enzyme that converts superoxide anion radicals into hydrogen peroxide and oxygen to prevent oxidative stress damage [ 39 ]. Studies have shown that dietary fiber contains the presence of some active substances (e.g., polyphenols) [ 40 ], which, as key components of dietary fiber, can exert antioxidant effects by complexing metal ions, increasing antioxidant enzyme activity, scavenging free radicals, and regulating the expression of signaling pathways, such as Nrf2/ARE [ 41 , 42 ], which is more consistent with the results obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…T-AOC is an important nonenzymatic antioxidant, and its decreased levels are associated with a reduced resistance of the body’s antioxidant defense system against free radicals [ 38 ]. T-SOD is a free radical scavenging enzyme in vivo key enzyme that converts superoxide anion radicals into hydrogen peroxide and oxygen to prevent oxidative stress damage [ 39 ]. Studies have shown that dietary fiber contains the presence of some active substances (e.g., polyphenols) [ 40 ], which, as key components of dietary fiber, can exert antioxidant effects by complexing metal ions, increasing antioxidant enzyme activity, scavenging free radicals, and regulating the expression of signaling pathways, such as Nrf2/ARE [ 41 , 42 ], which is more consistent with the results obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the last three years, Polygonatum sibiricum polysaccharides (PSP) are demonstrated to exhibit a wide range of pharmacological activity [ 21 ], such as osteogenic activity [ 22 ], anti-diabetes [ 23 ], immunological activity [ 24 ], and especially antioxidant activity, which makes them suitable for application in functional foods and therapeutic agents. PSP demonstrated strong antioxidant properties, which could attenuate D-gal-induced heart aging [ 25 ] and protect the mice livers against ethanol-induced oxidative damage via inhibiting oxidative stress [ 26 ]. However, no study has been reported using PSP as a decorator to functionalize SeNPs.…”
Section: Introductionmentioning
confidence: 99%
“…D-gal treatment decreased reactive oxygen species (ROS) and MDA and enhanced SOD levels in the hearts of mice. By reducing the levels of 8-hydroxydeoxyguanosine (8-OHdG) and 4-hydroxy-2-nonenal, PSP also prevented oxidative stress-induced DNA damage and lipid peroxidation (4-HNE) [ 67 ]. Regarding other species, extracts of P. alte-lobatum (EPA) dose-dependently reduced exercise-induced urea nitrogen and malondialdehyde and enhanced hepatic glycogen, an essential workout fuel [ 68 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%